1991
DOI: 10.1111/j.1432-1033.1991.tb16094.x
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding at membrane mimetic interfaces

Abstract: The behaviour of human serum albumin in the presence of three chemically distinct ligands: oxyphenylbutazone, dansylsarcosine and hemin, has been compared in buffer and in reverse micelles of isooctane, water, and either sodium bis(2-ethylhexyl)sulfosuccinate or hexadecyl trimethylammonium bromide, systems selected to mimic the membrane-water interface. Upon micellar incorporation, the dansylsarcosine-albumin complex dissociated, as evidenced by fluorescence emission spectroscopy (red shift from 485 nm to 570 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…attributed to a denaturation rnechanism. The problem \VUS in fact 1l10re complex as shO\VI1 later by the work of Desfosses et al (1991). These investigators found indeed a loss of intensity in both the near (not sho\vn) and the far-ultraviolet regions of the albuluin CD spectruIIl (Figure 14).…”
Section: Lysozyjllementioning
confidence: 82%
“…attributed to a denaturation rnechanism. The problem \VUS in fact 1l10re complex as shO\VI1 later by the work of Desfosses et al (1991). These investigators found indeed a loss of intensity in both the near (not sho\vn) and the far-ultraviolet regions of the albuluin CD spectruIIl (Figure 14).…”
Section: Lysozyjllementioning
confidence: 82%
“…The difference in binding is much too large to be attributed to the difference in molecular size of BSA relative to CHY and LYS. In addition, others have observed strong interaction between AOT and albumin (Desfosses et al, 1991;Marzola et al, 1991;Takeda et al, 1994). Second, the fit of the isotherm to the data in Figure 5 is poor relative to the data for CHY and LYS.…”
Section: Differences Between the Spe Of Lys Chy And Bsamentioning
confidence: 83%
“…Of interest, a recent report suggests that in the w o range 15-30 CHY solubilizes into w/o-MEs as dimers (Oldfield et al, 1996). However, the solubilization of either bovine or human serum albumin increases w/o-ME size (Desfosses et al, 1991;Takeda et al, 1994). Concerning LYS, a recent quasielastic light scattering study reports that its presence increased the size of w/o-MEs; however, their results did not take into account the contribution of interdroplet attractions occurring at the AOT concentration they employed (100 mM) to the measured scattered intensity (Chang et al, 1994).…”
Section: Effect Of Solid Protein Amountmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies revealed that BSA can transfer lipid amphiphile to the lipid bilayer membranes [6], reflecting that BSA could exert its function at the lipid-water interface. Moreover, several studies have suggested that membrane-interface or membrane-mimicking surface induces conformational changes in human serum albumin [7][8][9]. Taken together, these findings suggest that serum albumin could interact with the lipid bilayers.…”
Section: Introductionmentioning
confidence: 93%